AN INVESTIGATION OF THE CRITICAL THINKING ABILITIES OFNURSES IN GENERATION-X AND -Y: THE EXAMPLE OF ELAZIG - Uncu, Fatos; Evcimen, Hasan; Doğan, Ufuk (My University, 2021)
Aim: The aim of this study was to examine the critical thinking skills of working nurses in generation-X and -Y. Method: This descriptive cross-sectional study was conducted between 10.01.2019-01.03.2019 in a hospital in Elazıg province, and 107 nurses from different generations participated in the study. Generation-X was selected from nurses born between 1965 and 1979 and Generation-Y was selected from nurses born between 1980 and 1999. \"Personal Data Form\" and “California Critical Thinking Disposition Inventory” were used in the collection of data. Number, percentage, average, and t-test were employed to evaluate the data. Results: The average age of the nurses participating in the study was 33.42±7.45 and the average of their professional working duration was 10.86±7.65 years. Also, 58.9% of nurses were female, 74.8% were married, 68.2% had undergraduate and graduate degrees. Forty-three percent of the nurses in the study stated that they knew the concept of critical thinking also 57% of the nurses in the study were in generation-Y. The mean California Critical Thinking Disposition Inventory scores of the nurses were 224.64±20.83 and their critical thinking skills were found to be low. Nurses received the highest score from the sub-dimension of analyticity (45.75±5.64) and the lowest score from the sub-dimension of open-mindedness (29.41±6.41) among the sub-dimension of the California Critical Thinking Disposition Inventory scale. The critical thinking tendencies of Generation-Y nurses were higher than those of generation-X and a significant difference was found (p<0.05). Conclusion: Critical thinking ability, which is considered to be effective in clinical decision making, was found to be low in the nurses participating in the study. It is necessary to remove the obstacles to critical thinking of nurses in nursing programs and to develop a curriculum on critical thinking. It is proposed to provide in-service training to improve the critical thinking skills of working nurses
Keywords: Critical thinking; nursing; generation difference